A novel circRNA-miRNA-mRNA network revealed exosomal circ-ATP10A as a biomarker for multiple myeloma angiogenesis. Issue 1 (1st January 2022) - Yu, Manya; Yu, Jie; Zhang, Yanyu; Sun, Xiaoqi; Sun, Runjie; Xia, Mengting; Li, Sumei; Cui, Xing
ABSTRACT: The importance of angiogenesis in multiple myeloma (MM) is unquestionable; however, to date, the success of antiangiogenic therapies has been fairly limited. Exosomal circular RNAs (circRNAs) have been proven to be pivotal players in angiogenesis in various cancers. Nevertheless, their role in MM remains unknown. Therefore, we aimed to identify differentially expressed circRNAs in peripheral blood exosomes from MM patients and explore their diagnostic and prognostic values. We screened 2, 052 circRNAs with significant differential expression between MM patients and healthy controls via high-throughput sequencing. qRT-PCR confirmed that the expression of circ-ATP10A was significantly increased in MM patients. The bioinformatics analyses suggested that circ-ATP10A can act as a microRNA (miRNA) sponge and regulate the expression of downstream vascular endothelial growth factor-B (VEGFB), hypoxia-inducible factor-1alpha (HIF1A), platelet-derived growth factor subunit A (PDGFA), and fibroblast growth factor (FGF). The immunohistochemical results indicated that the circ-ATP10A level was positively correlated with the protein levels of VEGFB and marrow microvessel density (MVD) in MM patients, and the receiver operating characteristic (ROC) curve, area under the ROC curve (AUC) and Kaplan-Meier survival curve analyses confirmed it as a prognostic biomarker. Collectively, our study indicates that exosomal circ-ATP10A is a valuable prognostic biomarker in MM and may promote MM angiogenesis by targeting hsa-miR-6758-3p/hsa-miR-3977/hsa-miR-6804-3p/hsa-miR-1266-3p/hsa-miR-3620-3p and modulating their downstream mRNAs, such as VEGFB, HIF1A, PDGF, and FGF.